INDIAN NURSES IN THE GULF: TWO GENERATIONS OF FEMALE MIGRATION - Marie Percot (South Asia Research 2006; 26; 41, 2006)
The article, based largely on fieldwork in Gulf countries and in Kerala, focuses on female nurses from Kerala who have worked, are currently working or are preparing to work in Gulf countries. It examines in particular to what extent these women today aspire not only to a lucrative career abroad, but also to a new lifestyle in which traditional gender-based restrictions are replaced by increased and improved female agency and a focus on the nuclear family. The main goal of this article is to demonstrate how, after three decades, the migration of Keralese nurses to the Gulf has evolved into an actual migratory strategy to take advantage of the various new opportunities available in western countries. After two generations of nurse migration, evolutions, which are closely linked to the emergence of an Indian - or, more precisely, a Keralese - diaspora in the Gulf countries, are now taking on a much wider global dimension, with significant implications on lifestyle choices.